Understanding Malaysian ESL pre-service teachers’ beliefs about teaching and learning through metaphors - Wan Noor Miza Wan Mohd Yunus (Studies in English Language and Education, 2020)
Teaching metaphors are often used in teacher education programmes for pre-service teachers to critically reflect on their teaching. Metaphors not only give insights into teachers’ beliefs and principles about teaching and learning but may also guide classroom practices. This article sought to explore three Malaysian ESL pre-service teachers’ teaching metaphors in different situations during their teaching practicum. The study also explored what the selected metaphors revealed about the pre-service teachers’ pedagogical beliefs. Data in this study was collected qualitatively by using semi-structured interviews and reflective tasks assigned after the pre-service teachers’ teaching practicum at local government schools. Findings indicated that the pre-service teachers have multiple roles, which are represented by various metaphors they formulated in different situations. It has been suggested that metaphors can be effective in eliciting beliefs as the constructed metaphors reveal much about the roles of the pre-service teachers. The major beliefs about teaching and learning generated by the research participants include meeting students’ needs, varying teaching approaches, and facilitating students. The implications of this study are for teacher educators to utilize metaphors in teacher education programmes and to acknowledge pre-service teachers’ beliefs as this may highly impact their practices and development.